MODEL PROJECT BASED LEARNING BERBASIS APLIKASI MIMIND BERTEMA KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN MENULIS NARASI - Eli Nurliza; Erfinawati Erfinawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this study was to find out differences in learning outcomes for writing narratives for students of SMP 1 Darul Imarah Aceh Besar between students who took part in PJBL learning and students who used conventional learning. This research is using experimental method. Data collection was carried out through pretest and posttest. Data on increasing learning outcomes is in the form of normalized gain (N-Gain). The difference in the mean N-Gain of the experimental class and the control class was analyzed by independent sample t-test. The results showed that there were significant differences in student learning outcomes between the learning groups that took place using the PJBL model and the groups of students who were taught using conventional learning.